Consumption-based GHG emissions of the food supply chain in Japan: a top–down approach integrating input–output and margin tables - Osamu Kimura; Shunichi Hienuki (Environmental Research: Food Systems, 2025)
This study introduces an innovative top–down approach to evaluate greenhouse gas (GHG) emissions linked to food consumption in Japan. By combining input–output tables with supplementary margin tables, this method allows for a comprehensive assessment of consumption-based emissions across various stages of the food supply chain, including production, trade, and transportation. Applying this method to the Japanese food system, we found that food-related GHG emissions amounted to 220 million tonnes of carbon dioxide equivalent (t-CO2eq). Our methodology also enables the analysis of food consumption not only in households, but also in restaurants and food take-out services, finding that emissions from the meal-providing service sectors are 32 million t-CO2eq, compared to 159 million t-CO2eq from food directly purchased by consumers. Examination of these emissions highlighted the more significant role of meat consumption than previously recognized, although it remains much lower than that in Western countries. Additionally, we revealed that approximately 70% of food-related emissions occurred during the production phase, with the remaining 30% divided almost equally between the transport and retail processes. However, the distribution varied significantly depending on the type of food. These findings suggest the importance of reduction strategies during the production phase as well as changes in consumer behavior.